2020
DOI: 10.1111/appy.12390
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in long‐term hospitalization psychiatric wards in an equatorial nation

Abstract: Introduction: Vitamin D deficiency and insufficiency have been shown to be prevalent in several populations, including in people who have a mental illness. Deficiency has been linked to specific mental health sequelae. Furthermore, deficiency may be perpetuated by medications routinely prescribed to people with severe mental illness. Therefore, symptoms of mental illness may be exacerbated by deficient levels of vitamin D, and treatments for mental illness may exacerbate deficiency. This study sought to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 36 Studies have also shown that hospital in-patients from warmer latitudes with higher UV indices also have a propensity for vitamin D deficiency. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Studies have also shown that hospital in-patients from warmer latitudes with higher UV indices also have a propensity for vitamin D deficiency. 18 …”
Section: Discussionmentioning
confidence: 99%
“…9,10 People with intellectual and developmental disability (IDD) are likely to be at greater risk of developing these chronic illnesses 11 as well as being at increased risk of falls. 12 A number of primary studies have highlighted vitamin D insufficiency and deficiency among groups of people with IDD, [13][14][15] among institutionalised populations at a range of global latitudes [16][17][18] and among those with comorbid epilepsy, in part due to enzyme-inducing medication. 19 Studies among IDD populations have also investigated the risks of fractures and low bone mineral density, 20,21 potentially as the result of vitamin D insufficiency.…”
mentioning
confidence: 99%
“…Some data suggest that the psychiatric population has a higher rate of vitamin D deficiency than the general population [17,[23][24][25][26][27][28][29][30][31]. Patients from a psychiatric ward in Serbia have been included in a cross-sectional design study, and a significant number of patients had a lower vitamin D level than expected [30].…”
Section: Psychiatric Diseases and Vitamin Dmentioning
confidence: 99%
“…Patients from a psychiatric ward in Serbia have been included in a cross-sectional design study, and a significant number of patients had a lower vitamin D level than expected [30]. Even in an equatorial nation, despite the geographic location and outdoor activities, levels of vitamin D were still low among psychiatric hospitalized subjects [29].…”
Section: Psychiatric Diseases and Vitamin Dmentioning
confidence: 99%
“…However, in regions such as the Americas and Eastern Mediterranean countries, more than 25% of all inpatients with psychiatric disorders have stays exceeding one year [ 26 ]. Long-term hospitalisation and its challenges in transitioning to community-based care have surfaced as national concerns in countries such as India, Singapore, China, and South Korea since the 2010s [ 2 , 3 , 15 , 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%